Il Sé in psichiatria e in filosofia: una prospettiva storica - Fargnoli, Francesco (Il sogno della farfalla, 2016)
The article outlines a brief history of the concept of the self. In particular, it tries to answer the question of how the concept of the self was introduced and how it developed in psychiatry as well as which philosophers influenced psychiatrists such as Eugen Bleuler, Karl Jaspers, Kurt Schneider when they elaborated the concept of the self. Has psychiatry managed to shed a new light on the comprehension of what the self is, hence on the essence of human beings? Or, has it become stuck on the repetition of old formulae, which have been so skillfully hidden underneath linguistic artifices?